THE INFLUENCE OF COMPANY SIZE, INSTITUTIONAL OWNERSHIP, MEDIA EXPOSURE, MANAGERIAL OWNERSHIP AND CASH HOLDING ON INCOME - Dirvi Surya Abbas; Kimsen; Indriani Nour Fitriana; Siti Rahmah Nuraini; Siti Romdona (Fakultas Ekonomi Universitas IBA, 2025)
The Purpose Of This Study Is To Determine The Effect Of Company Size, Institutional Ownership, Media Exposure, Managerial Ownership, Cash On Income Smoothing. This Study Uses A Quantitative Approach, Panel Data Regression Analysis. The Study Sample Consists Of 175 Non-Cyclical Consumer Sector Companies With The Purposive Sampling Method. Research Results Show That Company Size And Institutional Ownership Have A Negative Impact On Income Smoothing Because High Company Size And Institutional Ownership Will Avoid Fluctuative Income Changes For Investors Who Will Liquid Their Shares, Media Exposure Has A Positive Impact On Income Smoothing Because High Media Exposure Can Reduce The Company's Income Smoothing, Managerial Ownership And Cash Holding Have No Influence On Income Smoothing Because It Can Experience Long-Term Losses While Cash Is Only Functional So It Does Not Can Be Used In Income Smoothing